LGG-38. Dose-dependent seizure control for an NF1 patient treated via MEK-inhibition for optic pathway glioma. (3rd June 2022) - Cantor, Evan; Meyer, Ashley; Ogle, Andrea; Shatara, Margaret; Cluster, Andrew; Abdelbaki, Mohamed S; Morris, Stephanie; Weisenberg, Judith; Brossier, Nicole M
Abstract: BACKGROUND: Low-grade gliomas (LGG) are the most common solid tumor of childhood and can result in neurologic complications, including seizures, focal neurologic deficits, and learning difficulties. Molecularly targeted agents are increasingly being utilized to treat LGG, but the effect of these agents on accompanying neurologic complications are poorly understood. CASE: An 8-years old male with Neurofibromatosis Type 1 (NF1), medically refractory epilepsy and deep extensive glioma (extending from the optic pathway and involving the basal ganglia and corpus collosum) began selumetinib therapy due to radiographic and symptomatic tumor progression. Radiographic response (resolution of enhancement) was observed at 12 weeks of therapy, accompanied by improvement in seizure frequency, hemiparesis, and academic performance. Due to cardiotoxicity observed at that time (asymptomatic decreased ejection fraction and shortening fraction on echocardiogram), selumetinib was reduced to 50% dosing. On this reduced dose of selumetinib, seizures increased in frequency with subsequent worsening hemiparesis and recurrence of learning difficulties. One month later, dosing was escalated back to 100% due to interval resolution of cardiotoxicity, resulting in resolution of seizures and improvement in focal neurologic deficits and cognition. DISCUSSION: Dose-dependent response to MEK inhibition was observed without concurrent changes in anti-epileptic medications. The tumor was stable in size despite improved enhancement with treatment, suggesting that objective response by RANO criteria is not necessary for improved seizure control in LGG. Recent work has implicated the RAS/MEK/ERK pathway in neuronal precursor cells as a cause for epilepsy, suggesting that MEK inhibition of NF1-heterozygous neurons could be contributing to treatment response in this patient. Improvements in weakness and academic performance may have been due to improved seizure control or a direct effect of MEK inhibition on NF1-heterozygous neurons. CONCLUSION: MEK inhibition may have a clinically relevant anti-seizure effect for patients with pediatric LGG or NF1.